PRESIDENTIAL SUCCESSION LAW IN CONSTITUTIONS OF ASIAN STATES: HUKUM SUKSESI KEPRESIDENAN DALAM KONSTITUSI NEGARA-NEGARA ASIA - Ramadhan, Febriansyah (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
Presidential succession law is a crucial constitutional instrument designed to ensure the continuity of government in the event of an unexpected vacancy in executive leadership (concurrent vacancy of the President and Vice President). Although such events are rare, their impact on political stability can be profound if not adequately anticipated within a constitutional framework. This article examines how South Korea and the Philippines have constructed their presidential succession laws. South Korea has experienced repeated executive vacancies, while the Philippines, despite sharing substantial similarities in governmental structure with Indonesia—both drawing significant inspiration from the United States Constitution—adopts a notably different succession framework. Using a doctrinal research method with a statutory and comparative constitutional approach, this study finds that both countries have established clear and multi-layered succession structures capable of preventing systemic disruptions even in crises such as presidential impeachments. By contrast, Indonesia’s succession design under Article 8(3) of the 1945 Constitution (UUD NRI 1945) reveals fundamental weaknesses, particularly in assigning collective authority to three ministers without a clear substitution mechanism, thereby exposing the state to the risk of a power vacuum. Nevertheless, the mechanism for electing a new President and Vice President through the People's Consultative Assembly (MPR) provides a pragmatic solution tailored to Indonesia’s complex geographical and political conditions. Based on these findings, the article advocates for a comprehensive reform of Indonesia’s executive succession framework through a concrete, operational, and adaptive institutional architecture to ensure that the machinery of government continues to function even under the most severe crises.